2013
DOI: 10.1177/1420326x13503841
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on one-side confined jets from a parallel-flow outlet in a push–pull ventilation system

Abstract: This study conducted a series of experiments on the airflow characteristics of one-side confined jets from a parallel-flow outlet with a two-tier perforated plate and a honeycomb in a push–pull ventilation system. Maximum velocity, maximum temperature and airflow trajectory were analysed and compared with previous studies about different outlets. The results showed that the dimensionless turbulence coefficient of the parallel-flow outlet was smaller than either the cased axial fan with open grille’s or the swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…41,42 In industrial premises, there has long time realized that only the near zone around workers would need to be protected from pollution and thermal stress. 43,44 Based on this, local exhaust ventilation 45,46 and push-pull ventilation strategies 47 have been widely used to directly remove the contaminant and heat. In operating theatres, only the local indoor environment for patients and medical personnel would need to be secured.…”
Section: Therefore Novelmentioning
confidence: 99%
“…41,42 In industrial premises, there has long time realized that only the near zone around workers would need to be protected from pollution and thermal stress. 43,44 Based on this, local exhaust ventilation 45,46 and push-pull ventilation strategies 47 have been widely used to directly remove the contaminant and heat. In operating theatres, only the local indoor environment for patients and medical personnel would need to be secured.…”
Section: Therefore Novelmentioning
confidence: 99%
“…In industrial buildings, only the zone around the products or workers needs to be protected from pollution and thermal stress [23][24] . Based on this, local exhaust ventilation [25][26] and push-pull ventilation [27] have been widely used to directly remove the contaminant and heat. In operating rooms and hospital wards, only the local indoor environment for patients and medical personnel needs to be secured [28] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Huang et al [9] found that increasing the jet-isolated flow rate can reduce moderately the spillage levels. In industrial production, the push-pull ventilation is widely used [10], [11], but it is rarely used for pollution control in the kitchen. Zhou et al [12] proposed a push-pull ventilation system for a residential kitchen, and they observed a capture efficiency improvement with a good air distribution in the kitchen area.…”
Section: Introductionmentioning
confidence: 99%